Tindak ilokusi komisif bahasa Indonesia dalam interaksi keluarga - Mudiono, Alif (citeus, 2010)
This research was aimed at describing as well as explaining certain types of Indonesian illocutionary acts, usages, and their impacts on family interactions. Communicative and pragmatic designs were used in the research. The results of the research indicate that Indonesian commissive illocutionary acts in family interactions include promises as well as bargain actions, and these actions can develop through various powers. They are implicated by the usage of the following principles: politeness, cooperation and values developing in the family. The principles are also influenced by the socio-cultural dimensions.